Governing the 'ungovernable'? Financialisation and the governance of transport infrastructure in the London 'global city-region'. (August 2019) - O'Brien, Peter; Pike, Andy; Tomaney, John
Highlights: Global city-regions dominate national political-economies and fuel uneven development. State actors are using speculative financial mechanisms to attract new capital. Entrepreneurialism and managerialism shaping urban infrastructure governance. Abstract: The governance of infrastructure funding and financing at the city-region scale is a critical aspect of the continued search for mechanisms to channel investment into the urban landscape. In the context of the global financial crisis, austerity and uneven growth, national, sub-national and local state actors are being compelled to adopt the increasingly speculative activities of urban entrepreneurialism to attract new capital, develop 'innovative' financial instruments and models, and establish new or reform existing institutional arrangements for urban infrastructure governance. Amidst concerns about the claimed 'ungovernability' of 'global' cities and city-regions, governing urban infrastructure funding and financing has become an acute issue. Infrastructure renewal and development are interpreted as integral to urban growth, especially to underpin the size and scale of large cities and their significant contributions within national economies. Yet, overcoming fragmented local jurisdictions to improve the governance and economic, social and environmental development of major metropolitan areas remains a challenge. The complex, and sometimes conflicting and contested inter-relationships at stake raise important questions about the role of the state in wrestling with entrepreneurial and managerialist governance imperatives. City and government actors are simultaneously engaging with financial actors, the financialisation of the built environment, the enduring and integral position of the state in infrastructure given its particular characteristics, the transformation of infrastructure from a public good into an asset class through the agency of private and state interests, and what relationships, if any, exist between 'effective' urban governance systems and improved economic performance. Contributing to theoretical debates about the apparent 'ungovernability' of global cities and city-regions, this paper presents analysis and findings from new research examining the financialisation and governance of transport infrastructure in the London global city-region. The continued rise in London's population is placing significant demands upon existing infrastructure assets and systems and provoking debates about the extent and nature of growth in the UK's capital, the development of and relationship between urban and sub-urban built environments, and the ability of national, sub-national and local actors to plan infrastructure renewal and investment both within London's formal administrative boundary and wider city-region. Combining aspects of urban entrepreneurialism and managerialism amidst the challenges of governing a global city-region, the search for new infrastructure investment by state actors is leading to the revival of specific funding and financing mechanisms and practices. The mixing of existing and new funding and financing techniques as well as governance arrangements in distinct and, at times, hybrid ways, is amplifying the novel challenges facing actors and institutions responsible for London's governance.